Payday - Yonathan A. Arbel (Washington University Law Review, 2020)
Legislation lags behind technology all too often. While trillions of dollars are exchanged in online transactions—safely, cheaply, and instantaneously—workers still must wait two weeks to a month to receive payments from their employers. In the modern economy, workers are effectively lending money to their employers, as they wait for earned wages to be paid. The same worker who taps a credit card to pay for groceries in semiautomated checkout lines depends on dated payroll systems that only transfer payments on a “payday.” Workers, especially those living paycheck-to-paycheck, are hard-pressed to meet their daily needs and turn to expensive, short-term credit products—notably, payday lenders. While the need for credit is a real one, credit providers charge a steep price, often culminating in endless debt spirals. So, why does the payday still exist? This Article studies various explanations—economic, historical, behavioral, and legal. A primary conclusion is that the payday owes its existence to legacy legal architecture. That is, payday is a software problem, not a hardware problem. The hardware—i.e., money and payroll technology—is here. We can pay workers daily; in fact, gig economy workers in developing countries will often be paid more quickly than an American employee for the same work. What holds us back is our legal software: dated Eisenhower-era legislation that failed to anticipate technological change. Surprisingly, even pro-worker legislation, such as minimum wage laws, inadvertently encourages the practice. By revealing the overlooked and dated legal infrastructure that sustains the payday, this Article suggests a path for legal reform. Daily streams of payment to workers are feasible, practical, and far more efficient than most people realize. A focused reform could effectively bring an end to the puzzling and pernicious practice of having workers lend money to their employers while they wait for their payday.
Keywords: Payday; Legal infrastructure; Law and economics; Credit; Payday lenders; Payroll technology; Employment law